(untitled) (Chichester, West Sussex, U.K., 2016)
Featuring a collection of original chapters by leading and emerging scholars, The Wiley-Blackwell Companion to Sociology presents a comprehensive and balanced overview of the major topics and emerging trends in the discipline of sociology today. Features original chapters contributed by an international cast of leading and emerging sociology scholars. Represents the most innovative and 'state-of-the-art' thinking about the discipline.
Keywords: Xã hội học,Sociology